Faceless, estranged and dangerous: visual representation of female migrants from the Middle East and Africa in the Serbian media landscape - Krstic, Aleksandra (Sociološki pregled, 2022)
Contemporary research on media reporting about migrants and refugees has been intensified since the 2015 European migrant crisis. However, only a limited number of authors focus on the visual representation of female migrants, which has been recognised to lead to more positive citizens’ perceptions and the development of the “culture of hospitality” (Bleiker et al., 2014). The main objective of this paper is to identify dominant visual frame in which female migrants appear in the Serbian print and online media. The mixed-method analysis of 54 images captured from 2015 until 2020 is based on the theoretical concept of visual media frames. The main results show that female migrants have been dominantly visually represented as a threat to border security and public health and that they are usually captured in long shots, deprived of identity and voice in the overall media coverage.
Keywords: visual media frames; female migrants; media; Serbia